Effect of Reduction in Thickness and Rolling Conditions on Mechanical Properties and Microstructure of Rolled Mg-8Al-1Zn-1Ca Alloy - Yuta Fukuda; Masafumi Noda; Tomomi Ito; Kazutaka Suzuki; Naobumi Saito; Yasumasa Chino (Advances in Materials Science and Engineering)
A cast Mg-8Al-1Zn-1Ca magnesium alloy was multipass hot rolled at different sample and roll temperatures. The effect of the rolling conditions and reduction in thickness on the microstructure and mechanical properties was investigated. The optimal combination of the ultimate tensile strength, 351 MPa, yield strength, 304 MPa, and ductility, 12.2%, was obtained with the 3 mm thick Mg-8Al-1Zn-1Ca rolled sheet, which was produced with a roll temperature of 80°C and sample temperature of 430°C. This rolling process resulted in the formation of a bimodal structure in the α-Mg matrix, which consequently led to good ductility and high strength, exclusively by the hot rolling process. The 3 mm thick rolled sheet exhibited fine (mean grain size of 2.7 μm) and coarse grain regions (mean grain size of 13.6 μm) with area fractions of 29% and 71%, respectively. In summary, the balance between the strength and ductility was enhanced by the grain refinement of the α-Mg matrix and by controlling the frequency and orientation of the grains.